2016
DOI: 10.1515/lingvan-2016-0026
|View full text |Cite
|
Sign up to set email alerts
|

Gender Change in Norwegian Dialects: Comprehension is affected before Production

Abstract: This article investigates language variation and change in the grammatical gender system of Norwegian, where feminine gender agreement is in the process of disappearing in some Northern Norwegian dialects. Speakers of the Tromsø (N = 46) and Sortland (N = 54) dialects participated in a Visual Word experiment. The task examined whether they used indefinite articles (en, ei, et) predictively to identify nouns during spoken-word recognition, and whether they produced feminine articles in an elicited production ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 20 publications
(30 reference statements)
1
19
0
Order By: Relevance
“…Yet another possibility is that the dialect speakers parse the native input with the grammar of the non-native dialect, something that may happen during dialect change due to large exposure to a national standard. The results from one previous Norwegian dialect study of gender processing (Lundquist et al, 2016 ) suggest that the latter is true, at least in dialect speakers that use Bokmål as their written standard. The dialect speakers in Lundquist et al ( 2016 ) used the three-gender system consistently in their productions, but were not able to predict upcoming nouns preceded by a masculine or feminine article.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Yet another possibility is that the dialect speakers parse the native input with the grammar of the non-native dialect, something that may happen during dialect change due to large exposure to a national standard. The results from one previous Norwegian dialect study of gender processing (Lundquist et al, 2016 ) suggest that the latter is true, at least in dialect speakers that use Bokmål as their written standard. The dialect speakers in Lundquist et al ( 2016 ) used the three-gender system consistently in their productions, but were not able to predict upcoming nouns preceded by a masculine or feminine article.…”
Section: Introductionmentioning
confidence: 93%
“…The results from one previous Norwegian dialect study of gender processing (Lundquist et al, 2016 ) suggest that the latter is true, at least in dialect speakers that use Bokmål as their written standard. The dialect speakers in Lundquist et al ( 2016 ) used the three-gender system consistently in their productions, but were not able to predict upcoming nouns preceded by a masculine or feminine article. These results suggested that the inconsistent use of the relevant articles encountered in written texts and in spoken input from other dialects had affected the processing of the native dialect.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…);Kupisch et al (2013);Lohndal and Westergaard (2016);Lundquist et al (2016);Urek et al (2017);Lundquist and Vangsnes (2018).…”
mentioning
confidence: 99%